PCA TRANSFORM FOR IMAGE ENHANCEMENT, COMPRESSION, AND CHANGE DETECTION - Ali, S.; Mahdi, A. (Iraqi Journal of Science, 2024)
The Principal-Components-Analysis (PCA) of KL-transform has been utilized as multi operators, (i.e. enhancement, compressor, and temporal change detector). Two images pair (Al-Jaderiya-Baghdad-Iraq) of 3-bands Landsat ETM+ (14.25 spatial-resolution) and Panchromatic Quick-Bird (0.6 meter) images are adopted to perform the PC analysis. Since most of the image band’s information are presented in the first PCs, therefore image classification and change detection procedures are performed with little consuming time. The linear “PCA” transformation can be used to translate and rotate data into a new coordinate system that maximizes the variance of the data. It can also be implemented for enhancing the information content.